Assessment of empathy among clinical dental students in a teaching dental institution in Telangana State, India - V Siva Kalyan; S Manjula; T Madhavi Padma; K. V. N. R. Pratap; P Vineela; Surya Chandra Varma (Wolters Kluwer Medknow Publications, 2017)
Introduction: The understanding of patient's view is considered as an important component in doctor-patient relationship. The health-care provider with an empathetic understanding may perceive patient's need as more reasonable and thus therapeutic. Aim: To assess empathy among clinical dental students in a teaching dental institution. Materials and Methods: A cross-sectional study was conducted among clinical dental students during the period between June 2016 and July 2016 in a teaching dental institution in Khammam town. Jefferson Scale of Empathy-Health Care Provider Student version was used to assess empathy among the students in this study. Gender differences were analyzed using t-test, and one-way ANOVA was used for comparison of empathy scores across year of study. P< 0.05 was considered statistically significant. Results: A total of 364 students participated in the study with a mean age of 22.76 ± 2.4 years. Males exhibited more empathy (86.54 ± 7) compared to females. The mean empathy level was found to be highest for the postgraduates (85.92 ± 6.5) followed by 3rd year students (P = 0.0943). Conclusion: There is a need to train these students not only from technical point of view but also in "life skills" such as communication, interpersonal relationship and empathy.